رقابة مجلس المنافسة على التجميعات االقتصادية في ظل االمر 30_30 - بوضياف خديجة - بوخلط منار (المسيلة, 2023)
التجسيع االقترادي يعتبخ الػسيمة األكثخ ضسانا لمػصػؿ إلى مدتػيات معتبخة مغ التشسية االقترادية. السؤسدات الكبخى في الجوؿ الستقجمة قبل السؤسدات الرغيخة و الستػسصة في الجوؿ الشامية فيػ حتسية فخضتيا الطخوؼ التشافدية داخل الدػؽ كسا أصبح شخيقة تمجأ إلييا نتيجة سعي األعػاف االقترادييغ لتحقيق مرالحيع الخاصة و عميو تجخل السذخع لتأشيخ و تشطيع عسمية التجسيعات االقترادية و ىػ ما تػصمشا إليو مغ خالؿ دراستشا ىحا السػضػع. Abstract: -economic grouping is the safest way to reach high levels of economic development. It is imperative imposed by the cometitive conditions within the market it hasalso become a method used by larg institutions in developed countries against small and medium-sized companies in devloping countries as a result of the purist of economic actors to achieve their own interests and the legislator must intervene to frame and regult them the process of economic groupings that we reached through our study this subject.
Keywords: رقابة مجلس المنافسة - التجميعات االقتصادية - ظل االمر 30_30